Towards a historical sociology of alms giving in “South African Islam” - Gotan, Rashid (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
In human history it is not uncommon for religious ideas to shape the behavioural attitude of actors within it. This paper finds its influences in Max Weber’s seminal essay The Protestant ethic and the spirit of capitalism. The quest of this paper is to investigate the formations of different forms of Islam in South Africa and how the ideas of early historical Islam at the Cape influences attitudes toward charity (sadaqa) and obligatory almsgiving (zakah). The Cape Islamic tradition is contrasted against the more doctrinal form of the religion in the provinces of KwaZulu-Natal and Gauteng. The methodology employed is historical-sociology which, in this case study, allows further comparison with the Dutch Reformed Church in the region and its attitude toward the “poor whites”. Conclusionary remarks are offered after three prominent Islamic organisations involved in Islamic forms of charity are investigated.